Local enterprises in the global economy issues of governance and upgrading - Schmitz, Hubert; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2004)
This book opens a fresh chapter in the debate on local enterprise clusters and their strategies for upgrading in the global economy. The authors employ a novel conceptual framework in their research on industrial clusters in Europe, Latin America and Asia and provide new perspectives and insights for researchers and policymakers alike.
1. Globalized localities : introduction -- 2. Regions in the "world economic triangle" -- 3. Making sense of global standards -- 4. Governance in global value chains -- 5. The underground revolution in the Sinos Valley : a comparison of upgrading in global and national value chains -- 6. How globalization affects Italian industrial districts : the case of Brenta -- 7. Upgrading in the tile industry of Italy, Spain and brazil : insights from cluster and value chain analysis -- 8. Local upgrading strategies in response to global challenges : the surgical instrument cluster of Tuttlingen, Germany -- 9. Clustering and upgrading in global value chains : the Taiwanese personal computer industry -- 10. Global quality standards and technological upgrading in the Brazilian auto-components industry -- 11. The effect of global standards on local producers : a Pakistani case study -- 12. Paradoxes and ironies of locational policy in the new global economy -- 13. Chain governance and upgrading : taking stock.
Includes bibliographical references and index.
Keywords: Small business; Small business -- Technological innovations; Corporate governance; Industrial location; Industrial concentration; Globalization -- Economic aspects; Electronic books